Human Capital Disclosure and Financial Performance: Evidence from Indonesian Resource-Based Public Companies - Ngadiman Ngadiman (PT. Mega Mas Abadi Konsultan, 2026)
Purpose: This study examines whether the quality of human capital disclosure is associated with firm financial performance among Indonesian public companies operating in resource-related industries. Design/Methodology/Approach: The study employs a quantitative secondary-data design using annual reports, sustainability reports, and audited financial statements. A Human Capital Disclosure Index (HCDI) is developed from publicly disclosed information covering workforce information, human capital development, talent management, employee welfare, and strategic human capital. Financial performance is measured using return on assets (ROA) and return on equity (ROE). Panel-data regression is used to test the association between HCDI and financial performance while controlling for firm size, leverage, growth, and firm age. Findings: The empirical analysis evaluates whether greater human capital transparency is associated with stronger asset and equity returns and whether the relationship differs across state-owned and private enterprises. Conclusion: The study positions human capital disclosure as a measurable bridge between human resource development and financial performance. Practical Implications: The framework provides managers and policymakers with a reproducible tool for assessing human capital reporting and its relationship with financial value creation.